Effect of Different Salinity on Osmolarity and Survival of Common Carp (Cyprinus carpio) with Fed Fermented Herbs - Rizki Putra; Henni Syawal; Morina Riauwaty (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Giving fermented herbs feed can increase appetite, feed digestibility, growth, and fish health. Rearing fish in salinity media aims to find the best salinity levels for osmolarity and survival, so that fresh water fish can also be reared in saline waters. This study used an experimental method with a completely randomized design (CRD), 5 treatment levels 3 replications, namely P0(0 ppt), P1(3 ppt), P2(6 ppt), P3(9 ppt), and P4(12 ppt). Salinity treatment was made by diluting seawater (35‰) with fresh water. The test fish used were common carp measuring 6-8 cm, kept in an aquarium measuring 60x40x40cm with a stocking density of 1 fish/3 liters of water. The feed given was in the form of commercial pellets plus fermented herbs at a dose of 200 mL/kg of feed dissolved in 500 mL of clean water. This research was conducted for 60 days. The results showed that the osmolarity of carp for 60 days of rearing ranged from 135-332 mOsm/kg H2O The highest absolute weight growth in P2 with a value (10.52 g) and lowest at P4 (8.36 g). The highest survival rate of carp was in the P0, P1 and P2 with a value (100%), while in P3(95%) and P4(75%). Common carp are able to tolerate salinity levels up to 12 ppt.